2015
DOI: 10.1021/acs.jpcb.5b10636
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Hydration Structure of Halide Ions: an Insight into the Importance of Lone Pairs

Abstract: An elusive tetrahedral hydration structure for bromide in aqueous solution has been unveiled through the use of ab initio molecular dynamics. It has been revealed that a subset of first shell water molecules has a preferential strong interaction with the ion lone pairs, giving rise to a tetrahedral short-lived complex. Through the use of a new geometric descriptor correlated to the ion-water pair interaction energy, we managed to divide the conventional first hydration shell into a tight first shell and a loos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 49 publications
3
31
0
Order By: Relevance
“…The exchange process rate has been evaluated by computing the mean residence times of both water molecules ( t WAT (2) ) and anions ( t X (2) ) in the Ln 3+ second coordination sphere (see Table ), by means of the Impey method . Following previous studies, ,, a t * value of 0.5 ps has been chosen to define a real exchange in the Impey procedure. All of the calculated residence times are of the order of magnitude of picoseconds, thus revealing the flexible nature of the La 3+ second solvation shell.…”
Section: Resultsmentioning
confidence: 99%
“…The exchange process rate has been evaluated by computing the mean residence times of both water molecules ( t WAT (2) ) and anions ( t X (2) ) in the Ln 3+ second coordination sphere (see Table ), by means of the Impey method . Following previous studies, ,, a t * value of 0.5 ps has been chosen to define a real exchange in the Impey procedure. All of the calculated residence times are of the order of magnitude of picoseconds, thus revealing the flexible nature of the La 3+ second solvation shell.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, at comparable sizes, anions induce a more pronounced perturbation of their hydration shells compared to cations, because they are hydrogen-bond acceptors. 17,50,113,268,282,294,[296][297][298][299][300][301][302] The same applies to small or/and multivalent ions, because they generate a stronger electric field at their surface. This more important perturbation may require the inclusion of the second hydration shell into the QM region.…”
Section: Discussionmentioning
confidence: 96%
“…In this respect, it is interesting to note that three recent approaches for improving the description of ion-water interactions at the MM level rely in effect on a weakening of the ion-solvent Coulombic interactions. These are: the induction-type 66,67,104,107,[278][279][280][281]284 force fields, where CT effects are included explicitly, the molecular dynamics in electric continuum (MDEC) approach, [285][286][287] where the ion charge is effectively scaled 75,[77][78][79]288 by a factor of about 0.7-0.9 (in line with QM results 282 ), and the multisite ion description, [289][290][291][292][293][294][295] where the ion charge is redistributed over virtual off-center sites within the ion. The observation made here that the features of the QM/MM RDFs can be reproduced more accurately with a MM model when reducing the nominal charge of the ion to +0.75 e is perfectly in line with these considerations.…”
Section: Discussionmentioning
confidence: 99%
“…And thus for the hydration of the [CaCl 4 ] 2– cluster, 12 water molecules were considered; 15 and 18 water molecules were considered for the [CaCl 5 ] 3– and [CaCl 6 ] 4– clusters, respectively. Recently, Sessa et al showed that the conventional first shell of a halide ion can be divided into a tight first shell and a loose shell . Such characteristics were taken into account for the construction of initiated hydrated structures of Cl – in [CaCl x ] 2– x ( x = 3–6) clusters.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, Sessa et al showed that the conventional first shell of a halide ion can be divided into a tight first shell and a loose shell. 69…”
Section: Dft Calculationsmentioning
confidence: 99%